CHEMICAL COMPOSITION OF GULKHYRI (ALTHAEA OFFICINALS L) PLANT, ELEMENT ANALYSIS OF GULKHYRI OIL AND ITS SIGNIFICANCE IN FOLK MEDICINE (Scientific journal of the Fergana State University, 2023)
In this article, the chemical composition of the oil of marigold (Althaea officinalis l) is fully explained and the "Cold pressing" method is used to fully preserve the beneficial chemical modes of marigold (Althaea officinalis l) oil. Using the "DD85-G" press equipment manufactured by the German company "AEN Engineering GmbH & Co.KG", the oil was extracted by pressing the quality seeds of sunflower cleaned in accordance with sanitary requirements, macro-micro element analysis Avio200 ISP–OES Inductively coupled was analyzed in a plasma optical emission spectrometer (Perkin Elmer, USA). The accuracy of the device is high, and it allows to measure the elements contained in the solution to an accuracy of 10-9g.